2020
DOI: 10.3389/fonc.2020.00332
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Breast Lesions and Distinguishing Their Histological Subtypes Using Diffusion-Weighted Imaging and ADC Values

Abstract: Diffusion-weighted imaging (DWI) has not been well explored in differentiation of malignant from benign breast lesions. The aims of this study were to examine the role of apparent diffusion coefficient (ADC) values in differentiation of malignant from benign tumors and distinguishing histological subtypes of malignant lesions, and to determine correlations between ADC values and breast tumors structure. This cohort-study included 174 female patients who underwent contrast-enhanced breast MR examination on a 3T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
2
11
1
Order By: Relevance
“…MRI can not only analyze the nature of the lesion through morphological features, but also obtain a variety of quantitative parameters using functional imaging sequences for more objective evaluation and diagnosis (6). Diffusion weighted MRI (DW-MRI), which indirectly reflects the degree of tissue differentiation and the integrity of cell membranes, is routinely used to improve the accuracy of differential breast lesion diagnoses (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…MRI can not only analyze the nature of the lesion through morphological features, but also obtain a variety of quantitative parameters using functional imaging sequences for more objective evaluation and diagnosis (6). Diffusion weighted MRI (DW-MRI), which indirectly reflects the degree of tissue differentiation and the integrity of cell membranes, is routinely used to improve the accuracy of differential breast lesion diagnoses (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The ADC model requires two bvalues to fit the curve. Many studies have shown that ADC has a certain significance in the identify of benign and malignant breast lesions (8,9). The intravoxel incoherent motion (IVIM) model is first proposed by Bihan et al (12) and has been reported to have good diagnostic performance for the diagnosis of pancreatic ductal adenocarcinoma (13).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, MRI has a high sensitivity but lower specificity (93% and 71%, respectively) [ 21 ] in the assessment of breast lesions. Recent studies [ 20 , 21 , 22 , 23 , 24 ] have suggested that the additional evaluation of the diffusion properties of breast lesions can improve specificity; ADC, measured in DWI, is thus being increasingly used as a marker in the detection and characterization of breast lesions [ 21 ]. Furthermore, other authors added to this additional ADC ratio calculation [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%